Hybrid energy systems : strategy for industrial decarbonization - Shah, Yatish T. (Boca Raton, FL : CRC Press, 2021)
"This book demonstrates how hybrid energy and processes can decarbonize energy industry needs for power and heating and cooling. It describes the role of hybrid energy and processes in nine major industry sectors and discusses how hybrid energy can offer sustainable solutions in each. Sectors include coal, oil and gas, nuclear, building, vehicle, manufacturing and industrial processes, computing and portable electronic, district heating and cooling and water. Written for advanced students, researchers, and industry professionals involved in energy-related processes and plants, this book offers latest research and practical strategies for application of the innovative field of hybrid energy"--
OCLC-licensed vendor bibliographic record.
Keywords: Renewable energy sources; Hybrid power systems; Renewable resource integration; TECHNOLOGY / Engineering / Chemical & Biochemical